Circulating Endothelial Cells From Septic Shock Patients Convert to Fibroblasts Are Associated With the Resuscitation Fluid Dose and Are Biomarkers for Survival Prediction. Issue 7 (July 2019) - Tapia, Pablo; Gatica, Sebastian; Cortés-Rivera, Cristian; Otero, Carolina; Becerra, Alvaro; Riedel, Claudia A.; Cabello-Verrugio, Claudio; Kalergis, Alexis M.; Simon, Felipe
Abstract : Objectives: To determine whether circulating endothelial cells from septic shock patients and from nonseptic shock patients are transformed in activated fibroblast by changing the expression level of endothelial and fibrotic proteins, whether the level of the protein expression change is associated with the amount of administered resuscitation fluid, and whether this circulating endothelial cell protein expression change is a biomarker to predict sepsis survival. Design: Prospective study. Setting: Medical-surgical ICUs in a tertiary care hospital. Patients: Forty-three patients admitted in ICU and 22 healthy volunteers. Interventions: None. Measurements and Main Results: Circulating mature endothelial cells and circulating endothelial progenitor cells from septic shock and nonseptic shock patients showed evidence of endothelial fibrosis by changing the endothelial protein expression pattern. The endothelial proteins were downregulated, whereas fibroblast-specific markers were increased. The magnitude of the expression change in endothelial and fibrotic proteins was higher in the septic shock nonsurvivors patients but not in nonseptic shock. Interestingly, the decrease in the endothelial protein expression was correlated with the administered resuscitation fluid better than the Acute Physiology and Chronic Health Evaluation II and Sequential Organ Failure Assessment scores in the septic shock nonsurvivors patients but not in nonseptic shock. Notably, the significant difference between endothelial and fibrotic protein expression indicated a nonsurvival outcome in septic shock but not in nonseptic shock patients. Remarkably, area under the receiver operating characteristic curve analysis showed that endothelial protein expression levels predicted the survival outcome better than the Acute Physiology and Chronic Health Evaluation II and Sequential Organ Failure Assessment scores in septic shock but not in nonseptic shock patients. Conclusions: Circulating endothelial cells from septic shock patients are acutely converted into fibroblasts. Endothelial and fibrotic protein expression level are associated with resuscitation fluid administration magnitude and can be used as biomarkers for an early survival diagnosis of sepsis. Abstract : Supplemental Digital Content is available in the text.